PERMASALAHAN DALAM PELAYANAN KEPADA PENGHAYAT KEPERCAYAAN TERHADAP TUHAN YANG MAHA ESA (PROBLEMS IN SERVICES FOR THE ADHERENTS OF THE BELIEF IN ONE GOD) - Herman Hendrik (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2019)
This article discusses the consequences of placing the management of the Belief in One God (the Belief) in Indonesian cultural policy. It is interesting to discuss bearing in mind that the Belief in one God is a “religion” for its adherents, to some extent. Besides that, government’s treatment also shows that the Belief in One God is a “religion”, exemplified by the policy on the identity card of the Belief adherents; which can be left unfilled. However, the policy on the Belief is handled by government institution responsible for cultural policy, which is the Directorate of the Belief in One God and Tradition, a unit under the Directorate General of Culture, the Ministry of Education and Culture. Studies on the Belief are dominated by studies on the aspects of the Belief itself, e.g. the meaning of God; while studies on the policy on the Belief, e.g. the impact of government policy on the Belief adherents’ life, are still rare. Accordingly, this paper is expected to contribute to the body of knowledge on the Belief. In doing so, this paper analyses problems in the delivery of service for the Belief adherents in several areas in Indonesia. The data used in this paper is a document on the result of evaluation of service delivery for the Belief adherents, released by the Directorate of the Belief in One God in 2016. The document shows kinds of services of the Belief adherents, legal basis, problems in the services, and the solutions from the parties involved. Keywords: The Belief in One God, adherent, religion, cultural policy